Preclinical development of BCG.HIVA2auxo.int, harboring an integrative expression vector, for a HIV-TB Pediatric vaccine. Enhancement of stability and specific HIV-1 T-cell immunity - Aakash Mahant; Narcís Saubi; Yoshiki Eto; Núria Guitart; Josep Ma Gatell; Tomáš Hanke; Joan Joseph (Taylor & Francis Group, 2017)
One of the critical issues that should be addressed in the development of a BCG-based HIV vaccine is genetic plasmid stability. Therefore, to address this issue we have considered using integrative vectors and the auxotrophic mutant of BCG complemented with a plasmid carrying a wild-type complementing gene. In this study, we have constructed an integrative E. coli-mycobacterial shuttle plasmid, p2auxo.HIVAint, expressing the HIV-1 clade A immunogen HIVA. This shuttle vector uses an antibiotic resistance-free mechanism for plasmid selection and maintenance. It was first transformed into a glycine auxotrophic E. coli strain and subsequently transformed into a lysine auxotrophic Mycobacterium bovis BCG strain to generate the vaccine BCG.HIVA2auxo.int. Presence of the HIVA gene sequence and protein expression was confirmed. We demonstrated that the in vitro stability of the integrative plasmid p2auxo.HIVAint was increased 4-fold, as compared with the BCG strain harboring the episomal plasmid, and was genetically and phenotypically characterized. The BCG.HIVA2auxo.int vaccine in combination with modified vaccinia virus Ankara (MVA).HIVA was found to be safe and induced HIV-1 and Mycobacterium tuberculosis-specific interferon-γ-producing T-cell responses in adult BALB/c mice. We have engineered a more stable and immunogenic BCG-vectored vaccine using the prototype immunogen HIVA. Thus, the use of integrative expression vectors and the antibiotic-free plasmid selection system based on "double" auxotrophic complementation are likely to improve the mycobacterial vaccine stability in vivo and immunogenicity to develop not only recombinant BCG-based vaccines expressing second generation of HIV-1 immunogens but also other major pediatric pathogens to prime protective responses shortly following birth.